Differential development of the ventral visual cortex extends through adolescence - Golarai, Golijeh; Liberman, Alina; Yoon, Jennifer M.; Grill-Spector, Kalanit (Frontiers in Human Neuroscience, 2010)
The ventral temporal cortex (VTC) in humans includes functionally defined regions that preferentially respond to objects, faces, and places. Recent developmental studies suggest that the face selective region in the fusiform gyrus (‘fusiform face area’, FFA) undergoes a prolonged development involving substantial increases in its volume after age 7 years. However, the endpoint of this development is not known. Here we used functional magnetic resonance imaging (fMRI) to examine the development of face-, object- and place-selective regions in the VTC of adolescents (12 – 16 year olds) and adults (18 – 40 year olds). We found that the volume of face-selective activations in the right fusiform gyrus was substantially larger in adults than in adolescents, and was positively correlated with age. This development was associated with higher response amplitudes and selectivity for faces in face-selective regions of VTC and increased differentiation of the distributed response patterns to faces versus non-face stimuli across the entire VTC. Furthermore, right FFA size was positively correlated with face recognition memory performance, but not with recognition memory of objects or places. In contrast, the volume of object- and place-selective cortical regions or their response amplitudes did not change across our age-groups. Thus, we found a striking and prolonged development of face-selectivity across the VTC during adolescence that was specifically associated with proficiency in face recognition memory. These findings have important implications for theories of development and functional specialization in ventral temporal cortex.